Aracaju na primeira metade do século XX : operariado feminino e história local - Jesus, Erica Andrade de (2021)
This study aimed to analyze aspects of the female working class trajectory during the first half of the twentieth century. The results made it possible to make connections between the history of the Industrial district, from the city of Aracaju and the State of Sergipe, allowing for the inclusion of local History, in the History lessons of Basic Education, through teaching sequences. The methodological approach consisted of the literature review, analysis of the literary work "The Corumbas," the rescue of journalistic reports of the following journals: Sergipe – Jornal, Gazeta Socialista and O Estado de Sergipe; visits to the Industrial District to the headquarters of Confiança Sport Association to the Public Archive of the State of Sergipe and to the Historical and Geographical Institute of Sergipe. Our theoretical references were, the Lei de Diretrizes e Bases da Educação Nacional (LDB-9394/96), the Parâmetros Curriculares Nacionais (1998) and the Base Nacional Comum Curricular (BNCC) for the understanding of themes related to education. To understand the issues related to the female working class, we used the works of Matos; Borelli (2012), Rago (1987), Soihet (2012) and Perrot (2006) and for Local History our theoretical contributions were the researches of Samuel (1990), Fonseca (2006) and Zarbato (2018). Through this work, we observe that the entry of Sergipe female workers into the productive market during the first half of the 20th century brought significant advances for women at the time, enabling them to new fields of activity. However, old problems continued to exist, such as sexual and moral harassment, pay gap between men and women and double working hours, inside and outside the home. We believe that this work can, through the rescue of the trajectory of the female working class, enable the approximation of the Local History of teachers and students, expanding the notions of citizenship and belonging, contributing for them to recognize themselves as historical subjects.